Crystal polymorphism and enhanced dielectric performance of composite nanofibers of poly(vinylidene fluoride) with silver nanoparticles. Issue 2 (3rd July 2012) - Shi, Naien; Duan, Juanjuan; Su, Jie; Huang, Fengzhen; Xue, Wei; Zheng, Chao; Qian, Yan; Chen, Shufen; Xie, Linghai; Huang, Wei
Abstract Composite nanofibers of poly(vinylidene fluoride) (PVF2) with silver nanoparticles are fabricated by electrospinning. According to the X‐ray diffraction patterns and Fourier transform IR (FTIR) spectra, the content of piezoelectric β‐polymorph of PVF2 is enhanced in the composite fibers of PVF2 and silver as compared with the pristine PVF2 raw materials and electrospun nanofibers. The differential scanning calorimeter (DSC) measurement indicates that the composite of PVF2 and silver has higher melting point and crystallization temperature than that of pristine PVF2 nanofibers. Moreover, the existence of silver nanoparticles greatly enhances the dielectric constant of PVF2 nanofibers and keeps a low dielectric loss simultaneously, which mainly relates to the internal fibrous structure of the composite. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2013